Influence of deposition conditions on the composition, texture and microstructure of RF-magnetron sputter-deposited hydroxyapatite thin films; Thin Solid Films; Vol. 591, pt. В : Selected papers from 16th International Conference on Thin Films, October 13-16, 2014, Dubrovnik, Croatia - Ivanova A. A. Anna Aleksandrovna; Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich; Depla D. (2015, 2015)
Title screen